The ethics of cloning and creating embryonic stem cells as a source of tissue for transplantation: time to change the law in Australia. - Savulescu, J (2000)
Every day, people die because there are insufficient tissues available for transplantation. The development of cloning and embryonic stem (ES) cell line technologies offers real hope for developing better sources of tissues for transplantation. Moreover, these new technologies may mean that damaged tissue (for example, after a stroke or heart attack) can be replaced with normal functioning tissue rather than scar tissue. Research into 'therapeutic cloning' and the development of ES cell lines is illegal in several States in Australia. It is time to review that legislation in order to allow destructive embryo research. My argument is that at least research should be allowed on spare embryos from assisted reproduction; that it is only one moral view (of several plausible ones) of the status of the embryo which precludes producing embryos for research; that this view is mistaken and so it is morally permissible to produce embryos for research into therapeutic cloning.